Analysis of Science Process Skills of Junior High School Students on The Concept of Elements, Compounds, and Mixtures Based on Education for Sustainable Development - Susilo Hardiyani; Fenny Roshayanti; Harto Nuroso; M. Syaipul Hayat (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to analyze students' science process skills in solving science questions at State Middle Schools in Blora. This research uses a qualitative descriptive method. The instrument used in this research was a SPS test question in the form of an essay. The research data was carried out quantitatively and qualitatively. The results of the study show that the SPS of students at State Middle Schools in Blora on the concepts of elements, compounds, and mixtures is in the low category with an average of 50%. Based on the nine indicators analyzed, observing indicators have an average percentage of 54%, grouping indicators have an average percentage of 45%, grouping indicators have an average percentage of 45%, interpreting indicators have an average percentage of 53%, forecasting indicators have an average -an average percentage of 55%, the indicator of asking questions has an average percentage of 49%, the indicator of formulating a hypothesis has an average percentage of 52%, the indicator of applying concepts has an average percentage of 47%, the indicator of communicating has an average the average percentage is 53%, and the indicator of designing an experiment has an average percentage of 35%. The average score and achievement value of students is that there are 24 students in the sufficient category and 8 students in the low category.